Dominant C2 Domain Epitope Specificity of Inhibitor Antibodies Elicited by a Heat Pasteurized Product, Factor VIII CPS-P, in Previously Treated Hemophilia A Patients without Inhibitors - Sawamoto, Yoshikatsu; Prescott, Richard; Zhong, Degang; Saenko, Evgueni L.; Mauser-Bunschoten, Eveline; Peerlinck, Kathelijne; van den Berg, Marijke; Scandella, Dorothea (Thrombosis and Haemostasis, 1998)
From June, 1990, to November, 1991, in The Netherlands and Belgium, 16 previously treated severe hemophilia A patients (PTP) developed inhibitors after exposure to factor VIII CPS-P, a new heat pasteurized product. A previously untreated patient (PUP) also developed an inhibitor to CPS-P. In inhibitor neutralization assays with recombinant fVIII C2 and A2 domain polypeptides, plasmas from 14 PTPs were ≥79% neutralized by C2 and <10% by A2, but the PUP plasma was partially neutralized by C2 (48%) and A2 (28%). Immunoprecipitation assays of the PTP and PUP plasmas with the fVIII heavy chain and with recombinant C2 and A3-C1 polypeptides confirmed that the C2 dominant immune response to CPS-P was found only in the PTPs. Competition of the binding of 2 inhibitors to 125I-CPS-P by unlabeled CPS-P and another plasma fVIII was similar, demonstrating that the antibody response was not directed to epitopes only present in CPS-P. We propose that the immunogenicity of the CPS-P C2 domain was altered by heat pasteurization.